Differential pupillary constriction and awareness in the absence of striate cortex. - Weiskrantz, L; Cowey, A; Barbur, J (1999)
The fact that the pupil constricts differentially to visual stimuli in the absence of changes in light energy makes it a valuable tool for studying normal function as well as residual capacity in hemianopic subjects. When pupillometrically effective stimuli such as equiluminant gratings or coloured patches with an abrupt onset and offset are presented to the 'blind' hemifield, a hemianopic subject with damage largely restricted to striate cortex (V1) sometimes reports being 'aware' of the transient onset/offset, although without 'seeing' as such. The question addressed here is whether the pupil still responds in the condition of blindsight in its strict sense--i.e. discriminative capacity in the absence of acknowledged awareness--when stimuli are deliberately designed to eliminate awareness. This was accomplished by making stimulus onset and offset slow and gradual. The results with a well-studied hemianope, G.Y., demonstrate that there is still a pupillary constriction to isoluminant achromatic gratings and red-coloured stimuli, although reduced in size, in the absence of acknowledged awareness.